Synthesis of photoluminescent β-Ga2O3 nanostructures using electrospinning method, and control of length-diameter ratio by calcination heating rates - Rodrigues, Aline Varella [UNESP]; Sabino, Naira Linhares [UNESP] (Springer Nature, 2019)
Nanofiber precursors of PVP-Ga(NO3)3 were synthesized through the electrospinning technique, and monoclinic β-Ga2O3 patterns were later obtained through the calcination method. During the annealing process, the nanofibers’ pores decreased, and their lengths were uniform up to several micrometers due to the surface-to-core extension that comprises the crystallization through Ostwald ripening process. Synthesis on the structure and morphology of materials were investigated using scanning and transmission electron microscopy equipped with an energy dispersive spectrometer, X-ray diffraction, Raman and Fourier-transform infrared (FTIR) spectroscopies. The β-Ga2O3 optical properties disclosed very broad and intense photoluminescence emission spectrum in the blue region of the wavelength, whose driving force was the presence of oxygen vacancies in the structures. Two types of Ga3+ ions (GaO6 octahedral and GaO4 tetrahedral chains) were demonstrated to come from different vibrations of Ga–O bonds in the Raman and FTIR spectra. And Ga3+–CO adducts formed on coordinatively Ga3+ ion located at edges and corners of β-Ga2O3 crystallites. Thus, successful results of this work included the control of length-diameter ratio by calcination heating rates, as well as the broad blue emission band, representing a strong potential of β-Ga2O3 materials in optoelectronic applications.